Analysis of echocardiographic data in pediatric patients undergoing surgical correction of aortic coarctation in western Paraná (Research, Society and Development, 2023)
The aortic coarctation (CoAo) is a congenital heart disease characterized by a narrowing of the aorta in any region that is located that between the aortic arch and the bifurcation of the abdominal aorta. When this malformation is suspected, echocardiography is the first exam to be performed to evaluate anatomical and functional aspects of this heart. Through this investigation it is possible to confirm the diagnosis and follow up the case, referring the patient for surgical correction. This article aims to evaluate and compare different postoperative patients with CoAo, seeking to identify echocardiographic variables prior to surgical treatment capable of interfering with the prognosis and increased risk of recoarctation. This was a retrospective observational study, with analysis of medical records of a private pediatric cardiology clinic in Cascavel-PR, between January 1st and December 31st, 2021. Echocardiographic, personal and surgical data were evaluated. Throught the variables analyzed, it is concluded that there is a predominance of males, absence of other cardiovascular diseases is associated with aortic recoarctation. PCA and other associated heart diseases are more present in patients for recoarctation.